32. MALNUTRITION STATUS AND RELATED FACTORS AMONG GASTROINTESTINAL CANCER PATIENTS UNDERGOING CHEMOTHERAPY AT UNIVERSITY MEDICAL CENTER HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of malnutrition and its associated factors among gastrointestinal cancer patients undergoing chemotherapy at the University Medical Center Ho Chi Minh city in 2025.Methods: A cross-sectional study was conducted on 103 gastrointestinal cancer patients receiving chemotherapy from March to May 2025. Convenience sampling was applied. Nutritional status was assessed using the PG-SGA tool.Results: The median age of participants was 59 (50-67) years old, with males accounting for the majority (63.1%). Based on PG-SGA, 63.1% were either at risk of malnutrition or severely malnourished. A statistically significant association was found between nutritional status and cancer stage.Conclusion: The prevalence of malnutrition among gastrointestinal cancer patients undergoing chemotherapy is notably high. Early nutritional screening and timely interventions are essential to improve patient outcomes.
Keywords: Gastrointestinal cancer; chemotherapy; malnutrition.